2019
DOI: 10.4025/actasciagron.v41i1.42608
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microtomography in comparison to radiographic analysis of mechanically damaged maize seeds and its effect on seed germination

Abstract: Among the most relevant aspects of seed production, mechanical damage may affect seed germination and reduce health and vigor. This study introduces a noninvasive high-resolution imaging procedure for evaluating the mechanical damage to maize seeds and the effects on seed germination. Seeds with different levels of mechanical damage were evaluated using a benchtop micro-computed tomography system (micro-CT) and digital X-ray equipment. The two-dimensional transaxial, coronal and sagittal micro-CT sections were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…The results from the study showed that X-ray significantly affected plant growth (plant height and plant dry matter) and some growth indices (crop growth rate, relative growth rate, absolute growth rate, and leaf area ratio), yield and yield components (number of seeds, weight of seed and grain yield) of maize as well as nutritional value of the crop. The findings were similar to several studies conducted on different crops which proved the ability of X-radiation to cause important physiological and morphological changes such as root growth (Jain et al, 2010), percentage of seed germination (Sheppard and Chubey, 1990;Cicero et al, 1998., Gomes-Junior et al 2019) and leaf growth (Sheppard et al, 1987), thus confirming that the use of radiation may be helpful to improve grain yield in maize through mutation breeding program.…”
Section: Discussionsupporting
confidence: 87%
“…The results from the study showed that X-ray significantly affected plant growth (plant height and plant dry matter) and some growth indices (crop growth rate, relative growth rate, absolute growth rate, and leaf area ratio), yield and yield components (number of seeds, weight of seed and grain yield) of maize as well as nutritional value of the crop. The findings were similar to several studies conducted on different crops which proved the ability of X-radiation to cause important physiological and morphological changes such as root growth (Jain et al, 2010), percentage of seed germination (Sheppard and Chubey, 1990;Cicero et al, 1998., Gomes-Junior et al 2019) and leaf growth (Sheppard et al, 1987), thus confirming that the use of radiation may be helpful to improve grain yield in maize through mutation breeding program.…”
Section: Discussionsupporting
confidence: 87%
“…With the use of specific software, seed fractions in longitudinal and cross sections can be analyzed on the computer screen, increasing the chances of identifying mechanical damage that is difficult to visualize in X-ray (two-dimensional) images. Thus, image analysis using the micro-CT technique was effective for identifying injuries not observed in the X-ray test and highlights the effectiveness of this technique in studies on mechanical damage in seeds, as observed by other researchers (Gomes-Junior et al, 2019).…”
Section: Resultssupporting
confidence: 69%
“…If the surfaces are exposed to moisture and microorganism in the air, toxic chemicals such as aflatoxins might be produced (Pitt, Taniwaki, & Cole, 2013), which threatens the food safety. Furthermore, if the damaged kernels are used as seeds, the germination rate might be affected (Gomes Junior, Cícero, Vaz, & Lasso, 2019) and thus reducing the grain yield. Consequently, the kernel damage should be controlled at the first place in order to avoid these disadvantages.…”
Section: Introductionmentioning
confidence: 99%